Association of Stress Coping Strategies and Leisure Time Physical Activity with Academic Performance in Medical Students - Mohsin Mahmood, Mohammad Talal Afzal , Abdur Rehman Malik , Adam Umair Ashraf Butt , Muhammad Sarfraz Khan , Muhammad Haseeb Waseem, Mohsin Mahmood, Mohammad Talal Afzal , Abdur Rehman Malik , Adam Umair Ashraf Butt , Muhammad Sarfraz Khan , Muhammad Haseeb Waseem (Journal of Rawalpindi Medical College, 2021)
Background: In recent times, the incidence of stress has increased dramatically, and it is now becoming prevalent in students as well. This study aims to identify different coping strategies and leisure-time physical activity in medical students, and their association with academic performance throughout the stressful event of professional examinations using the brief Coping Orientation to Problems Experienced (COPE) inventory. Materials and Methods: It is a cross-sectional correlational study done during August 2019 to November 2019. Students enrolled in Bachelor of Medicine, Bachelor of Surgery (MBBS) studying at Rawalpindi Medical University, Pakistan participated in this research during their professional examinations. Independent sample t-tests were used to identify differences between the two academic groups (high and low achievers) by coping strategies, like approach coping and avoidant coping. The Spearman’s rho test was applied to find correlation between leisure time activity and academic status of students. High achievers were defined as those with average scores greater than 70% (and distinction, if any). Those with scores less than 70% (and supplementary exams taken if any) were classified as low achievers. Results: The majority of participants were females 259 (56.4%). Out of 459 students, 225(49%) were high achievers, while 234(51%) were low achievers. A weak negative correlation was established between sedentary/insufficiently active lifestyle (r (2) =0.114, P=0.015) and academic status. The mean scores of approach coping (mean =30.80, SD=5.32) were significantly higher for high achievers. By comparison, the mean scores of avoidant coping (mean =48.75, SD=4.92) were considerably higher for low achievers. Conclusion: A medium level of leisure-time physical activity and approach coping strategies such as active coping, emotional support, and diligent planning have considerable positive effects on performance.